Mapping the Intellectual Structure of Agile Leadership and Organizational Agility in Higher Education: A Bibliometric Review - Wresni Pujiyati; Badrudin; Nasir (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Higher education institutions are increasingly required to develop adaptive leadership and organizational capabilities in response to digital transformation, institutional complexity, and environmental uncertainty. This study aims to map the intellectual structure of research on agile leadership and organizational agility in higher education through a bibliometric review. Bibliographic data were retrieved from the Scopus database and screened using the PRISMA 2020 flow diagram. The final corpus consisted of 141 Scopus-indexed documents published between 2003 and 2026. The data were analyzed using VOSviewer to examine annual publication trends, keyword co-occurrence, co-authorship networks, country collaboration, and co-citation structures. The findings show that scholarly attention to this topic has increased substantially after 2021, with 103 documents published between 2021 and 2026. Keyword co-occurrence analysis reveals that the field is strongly shaped by dynamic capabilities, organizational agility, digital transformation, knowledge management, and innovation, while agile leadership remains an emerging but increasingly relevant theme. Co-authorship analysis indicates fragmented collaboration among authors, while country collaboration shows international distribution with uneven network connections. Co-citation analysis confirms that the intellectual foundation of the field is interdisciplinary, combining dynamic capabilities, resource-based view, strategic management, adaptive leadership, and university innovation studies. This study contributes to higher education management literature by clarifying the conceptual structure, collaboration patterns, and theoretical foundations of agility-related research in higher education.